2014
DOI: 10.1016/j.jped.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory viral infections in pediatric cancer patients undergoing chemotherapy

Abstract: the prevalence of respiratory viruses was relevant in the infectious episode, with no increase in morbidity and mortality. Viral co-detection was frequent in patients with cancer and ARIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
(22 reference statements)
4
22
0
1
Order By: Relevance
“…5,[12][13][14][15] Rhinovirus rather than RSV and parainfluenza virus was the most frequent cause of RVI, consistent with the results of recent studies using PCR tests. 5,6,[12][13][14][15][16] RVI investigation should be considered in immune compromised patients complaining of community-acquired respiratory symptoms, preferably in those with rhinorrhea or sputum predominant over a cough. If we consider that early termination of empirical antibiotic therapy led to a favorable outcome in children and adolescents with NF and RVI in a recent report by Santolaya et al, 15 early diagnosis of RVI by a PCR test in these patients can help to avoid an unnecessary antibiotic use.…”
Section: Comparison Between Patients With Upper and Lower Respiratorysupporting
confidence: 84%
See 2 more Smart Citations
“…5,[12][13][14][15] Rhinovirus rather than RSV and parainfluenza virus was the most frequent cause of RVI, consistent with the results of recent studies using PCR tests. 5,6,[12][13][14][15][16] RVI investigation should be considered in immune compromised patients complaining of community-acquired respiratory symptoms, preferably in those with rhinorrhea or sputum predominant over a cough. If we consider that early termination of empirical antibiotic therapy led to a favorable outcome in children and adolescents with NF and RVI in a recent report by Santolaya et al, 15 early diagnosis of RVI by a PCR test in these patients can help to avoid an unnecessary antibiotic use.…”
Section: Comparison Between Patients With Upper and Lower Respiratorysupporting
confidence: 84%
“…Recent studies on RVI in immune compromised children showed low mortality due to RVI, 0-3%. 5,[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]19 Fortunately, there was no death due to RVI in this study. This favorable outcome may be attributed to a growing concern for RVI in physicians, increasing diagnostic rates especially of mild RVI cases using PCR tests, and improved supportive care in immune compromised patients.…”
Section: Comparison Between Patients With Upper and Lower Respiratorymentioning
confidence: 95%
See 1 more Smart Citation
“…Collected nasopharyngeal aspirates were tested for RVI by rapid test (for influenza virus) and multiplex real-time PCR. Results showed that rhinovirus, RSV A and B, HMPV A and B, influenza B, coronavirus 229, coronavirus 43, influenza A, coronavirus 63, parainfluenza and influenza A/H1N1 were responsible for acute RVI (30). Clinical outcomes of HRSV infection also were studied among immunocompromised outpatient children with hematologic malignancy, solid organ transplant or hematopoietic cell transplant.…”
Section: Human Respiratory Syncytial Virus (Hrsv)mentioning
confidence: 99%
“…Second to rhinovirus, the most represented virus is HRSV, found in 2.1-46% of cases. HMPV has been found in 3.3-13.5% of cases, being classified as the third [19], fourth [18,[20][21][22][23], fifth [24] and tenth [25,26] most frequent respiratory virus, according to the literature reviewed. Interestingly, HMPV has been reported as the only viral agent that was responsible for an outbreak in a pediatric oncology population [27] (Table 1).…”
Section: Distribution Of Respiratory Viruses In Pediatric Cancermentioning
confidence: 99%